Ethics In Research and the Role of Librarians to Overcome Ethical Challenges: Exploring the Role of Librarians in Overcoming Ethical Challenges in Research (Journal of Advances and Scholarly Researches in Allied Education, 2014)
“Ethics or simple honesty is the building blocks uponwhich our whole society is based…” Kerry Stokes The philosophical examination from a moral standpointthat is matters of moral judgment may be called ethics in general terms. Wetherefore strive for excellence in the profession by maintaining and enhancingboth- our skills and knowledge. Ethics is a code of values which guide ourchoices and actions and determine the purpose of our lives. The present paper aims to highlight on ethics in researchwhich are partially associated with standards related to the research process,highlighting the role of the librarians to overcome ethical challenges.